Landscapes of desire in the poetry of Vittorio Sereni - Southerden, Francesca Emily, 1979- (Oxford : Oxford University Press, 2012)
This is the first book-length study in English on Vittorio Sereni (1913-83), a major figure in Italian 20th-century poetry. It argues that a key innovation of Sereni's poetry is the way in which it reworks the boundaries of poetic space to construct a lyric 'I' radically repositioned in the textual universe with respect to its predecessors.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Sereni, Vittorio -- Criticism and interpretation; Liminality in literature